Pagbalangkas sa Arkitekturang Filipino: Alternatibong Kritikal na Tema sa Historyograpiyang Arkitektural - Cabalfin, Edson Roy G. (Humanities Diliman: A Philippine Journal of Humanities; Vol 1 No 2 (2000), 2007)
There is a need to restudy and reframe the methodologies we use to present the history of Filipino Architecture. The paper is rooted in the idea that the current approach to historiography of Filipino architecture renders architecture itself irrelevant and detached from the students of architectural history. Postcoloniality is seen here as a conscious break from traditional notions of historiography and a means of empowerment for the marginalized. In Filipino Architecture, this implies a non-elitist and anti-auratic approach in looking at architecture. Furthermore, there is also a shift in looking at architecture not just as mere products, but more importantly as a process. In lieu of the popular diachronic-historic approach to architectural history writing, a synchronic-thematic system is proposed. To understand further the relevance of architecture to the lives of the Filipino, five critical themes were proposed as alternative ways of looking at architecture. The themes are: Architecture as Signifier of Places and Settings; Architecture as a Mode of Signifying Meaning; Architecture as Process of Creativity; Architecture as Adaptation and Adjustment to the Environment; and Architecture as Sites of Power Relations. With these critical themes, Filipino architecture is seen as a means of empowering the Filipino instead of being the source of oppression.